Optimalisasi Pertumbuhan Ekonomi Daerah dengan Analisis Sektor Unggulan di Papua - Ayu Dita Kurniawati; Hendry Cahyono (Jurnal Ekonomika : INDEPENDEN, 2022)
The purpose of this research is to find out the leading sectors in Papua Province to support optimizing the existing economy in the Papua region, where this research uses descriptive quantitative methods. The research data used is Papua Province's GRDP and National GDP in 2019 - 2021. The analysis technique used is LQ analysis, Shift Share, Klasen Typology and then concluded with Overlay analysis. The results obtained by the first priority sector to optimize Papua's GRDP are the mining and quarrying sector as well as the health services and social activities sector. The sector that can be the first priority has good progressive growth, a large contribution, and has competitiveness at the national level. The second priority is the construction sector, the transportation and warehousing sector, the government administration sector, defense and compulsory social security. The third priority is the electricity and gas procurement sector, the information and communication sector and the real estate sector. And other sectors become the fourth priority.